1969
DOI: 10.1113/expphysiol.1969.sp002011
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Chemical Control of Breath Holding

Abstract: A method is described for the study of breath holding in which the breath holds are separated by rebreathing to enable accurate control of pCO2; its theoretical basis is discussed.At the end of a breath hold, rebreathing a mixture such that the pCO2 continues to rise, nevertheless permits the breath hold to be resumed. The number of breaths during the rebreathing is unimportant and a single breath permits as long a resumed breath hold as five breaths.Healthy adult males held their breath at residual volume. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1969
1969
2001
2001

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 13 publications
2
25
0
Order By: Relevance
“…Although we only used three subjects, each served as his own control, and each breath holding-CO2 response curve was based on three or more breath holds. We have found that the relationship between breath holding time and initial PCO2 remains very constant for any one subject, with a coefficient of variation for the slope of 8-6 per cent and for the intercept of 2-8 per cent [Godfrey and Campbell, 1969]. The data on which these calculations were based, were obtained on one of the subjects (D.W.) of the present study.…”
Section: Resultsmentioning
confidence: 50%
See 3 more Smart Citations
“…Although we only used three subjects, each served as his own control, and each breath holding-CO2 response curve was based on three or more breath holds. We have found that the relationship between breath holding time and initial PCO2 remains very constant for any one subject, with a coefficient of variation for the slope of 8-6 per cent and for the intercept of 2-8 per cent [Godfrey and Campbell, 1969]. The data on which these calculations were based, were obtained on one of the subjects (D.W.) of the present study.…”
Section: Resultsmentioning
confidence: 50%
“…The experiments described here, in the previous paper [Godfrey and Campbell, 1969] and by Fowler [1954] all argue against specific chemical or lung volume thresholds for the breaking point of breath holding, or any constant relationship between final pCO2 and volume. The earlier finding of such a relationship [Mithoefer, 1959] can be explained by the fact that all his breath holds were begun at approximately the same pCO2 and with a larger lung volume the breath holding time increased and hence the final pCO2 was higher.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations
“…These are based on rebreathing C02:02 mixtures from a small bag (Read, 1967; Godfrey & Campbell, 1969 …”
Section: Introductionmentioning
confidence: 99%